Time-series prediction of sea level change in the east coast of Peninsular Malaysia from the supervised learning approach - Lai V.; Malek M.A.; Abdullah S.; Latif S.D.; Ahmed A.N. (International Information and Engineering Technology Association, 2023)
Decision making; Forecasting; Learning algorithms; Support vector machines; Support vector regression; Surface waters; Tide gages; Correlation coefficient; Marine management; Meteorological parameters; Regression support vector machines; Sea surface temperature (SST); Supervised learning approaches; Tide gauge data; Time series prediction; Sea level